THE ROLE OF THE COOPERATIVE, SMALL AND MEDIUM ENTERPRISES OFFICCE IN EMPOWERING MSMES IN SUKABUMI REGENCY - Fanisya Dewi Rahmalia; M Rijal Amirulloh; Dine Meigawati (DIA: Jurnal Administrasi Publik, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a very important sector and make a great contribution to realizing regional economic development. MSMEs are small business initiatives established by the community. MSMEs help economic growth, increase job opportunities, reduce unemployment, create new jobs, increase the country's foreign exchange, and support regional development. This study aims to discover the Role of the Cooperatives, Small and Medium Enterprises Office in empowering MSMEs in Sukabumi Regency. The method used in this study uses a descriptive qualitative research method. The researcher used the Gede Diva Theory, 2009, to examine the role of the government as a facilitator, regulator, and catalyst. The study results show that the Cooperatives, Small and Medium Enterprises Office has carried out its role to the maximum as a facilitator, regulator, and catalyst.